TLC determination of some flavanones in the buds of different genus Populus species and hybrids - Pobłocka-Olech Loretta; Migas Piotr; Krauze-Baranowska Mirosława (Acta Pharmaceutica)
Flavonoids in the buds of eight Populus species and hybrids were detected and compared with the aid of an optimized TLC method. Separation of 17 flavonoid aglycones belonging to different groups, namely, flavones, flavonols, flavanones and flavanonols, previously described as constituents of poplar buds, was performed on silica gel plates using a hexane/ethyl acetate/formic acid (60:40:1.3, V/V/V) mixture as the mobile phase. Pinocembrin and pinostrobin were found in the majority of analyzed poplar buds. For quantitative analysis of both compounds, two TLC evaluation modes, densitometric and videodensitometric, were compared and the established methods were validated. Concentrations of flavanones in some extracts differed slightly or significantly due to the analyzed plant matrix complexity and the TLC evaluation mode applied. Poplar buds rich in flavanones originated from P. × canadensis ‘Robusta’ (1.82 and 2.23 g per 100 g, resp.) and P. balsamifera (1.17 and 2.24 g per 100 g, resp.).